Designing a sustainability program pathway for the Grinsing weaving industry: a prospective MULTIPOL approach - Sakrianti, Lilian Avita; Saskara, Ida Ayu Nyoman (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
Grinsing weaving, a traditional art form unique to Bali, represents a significant aspect of the island's cultural heritage. This study aims to analyze the sustainability of the Grinsing weaving industry program by developing scenarios and formulating recommendations. Primary data were collected through surveys and Focus Group Discussions (FGDs) with 19 craftsmen and stakeholders. The MULTIPOL approach was employed for the analysis. The results indicate that the sustainability of the Grinsing weaving industry can be enhanced through policy scenarios focused on strengthening institutions and regulations to protect nature, customs, and culture, as well as developing the skills of craftsmen. This research provides valuable insights for stakeholders in shaping the development policies for the Grinsing weaving industry at the research site.